The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.29074/ascls.29.4.227
|View full text |Cite
|
Sign up to set email alerts
|

An Evidence-Supported Medical Laboratory Science Program Admissions Selection Process

Abstract: MedicalLaboratory Science program experienced a higher than desired student attrition rate due to a number of academic and non-academic student readiness factors. In an attempt to address retention and other issues, the program completed a curriculum update and revision as well as a conversion to a hybrid or flipped classroom delivery model, but in spite of an overall improvement in student learning outcomes, the program still experienced a high level of student attrition. Program faculty then developed and im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…However, a faster trajectory to graduation is desirable, as passing BOC scores are more likely in graduates who take the exam no later than 90 days after graduation. 9…”
Section: Time To Degree Completionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a faster trajectory to graduation is desirable, as passing BOC scores are more likely in graduates who take the exam no later than 90 days after graduation. 9…”
Section: Time To Degree Completionmentioning
confidence: 99%
“…However, an evaluation of over 9000 BOC scores in MLS showed higher scores in graduates who took the exam no later than 90 days after graduation. 9 In nursing, no significant differences in age, gender, and student success were found in traditional vs online students. 13 However, the same study showed that faceto-face students finished at a significantly faster pace and were generally younger than online students.…”
Section: Introductionmentioning
confidence: 97%